Collaborative Governance dalam Mewujudkan Kota Singkawang Sebagai Kota Tertoleran Tahun 2023 - Prihatiningsih, Meiga Dwi; Deliarnoor, Nandang Alamsah; Hermawati, Rina (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Tolerance is one of the essential pillars in creating a harmonious and inclusive society, particularly in a city with ethnic and cultural diversity like Singkawang. Collaborative Governance, as an approach involving various stakeholders in the decision-making process, is key to achieving this goal. This study aims to explore how Collaborative Governance plays a role in making Singkawang a Tolerant City in 2023, using Ansell and Gash's (2007) theory of Collaborative Governance as an analytical framework. The research method used is a qualitative study with a descriptive approach. Data was collected through in-depth interviews and related document analysis. The results show that there are 13 main stakeholders involved, with the Singkawang City Government as the primary facilitator. Each has a specific role in facilitating cooperation, conducting dialogues, preserving culture, and supporting activities that promote tolerance. The study also found that the roles and contributions among stakeholders have not yet been fully integrated into a structured legal framework, and there are still challenges in aligning interests and long-term commitments. Collaborative Governance in Singkawang is effective in enabling better coordination among stakeholders, but there are still shortcomings in dialogue participation, consensus on mutual understanding, and accountability mechanisms that need improvement. This study provides important insights for the development of public policy and collaborative practices in Singkawang.